Exploring Learning Obstacles in Extraction: A Qualitative Analysis for Systems Thinking-Based Didactical Design - Annisa Khairani Putri; Hernani Hernani; Soja Siti Fatimah; Atep Rian Nurhadi; Billy Oktora Abdilah Fauzi (Jurnal Tadris Kimiya, 2026)
Despite the fundamental role of extraction in chemical analysis, pre-service chemistry teachers often struggle to move beyond procedural understanding toward a holistic grasp of the chemical system. Traditional instruction frequently overlooks the complex interdependencies within extraction processes, creating significant learning barriers. This qualitative preliminary study analyzes learning obstacles (ontogenic, epistemological, and didactic) in the extraction material as a critical step in developing a Systems Thinking-based didactical design. The study also aims to identify how these barriers hinder students’ ability to connect conceptual, procedural, and representational aspects of extraction processes, as well as to provide an empirical foundation for designing more integrative and meaningful chemistry learning experiences. By exploring students’ cognitive difficulties and instructional challenges, this research seeks to support the development of pedagogical strategies that promote system thinking, conceptual integration, and contextual understanding in analytical chemistry education. Data was collected through in-depth interviews with eight pre-service chemistry teachers who had completed Analytical Chemistry courses. The findings reveal that ontogenic obstacles, characterized by fragmented prerequisite knowledge and cognitive unreadiness, are the primary inhibitors of systems thinking. Specifically, students fail to visualize extraction as a dynamic system, leading to a disconnect between macroscopic observations and sub-microscopic interactions (epistemological barriers). Furthermore, didactic obstacles stemming from linear instructional methods were found to reinforce these fragmented mental models. This study concludes that overcoming these complex barriers requires a shift toward system-oriented pedagogical frameworks. Implementing learning-based problem integration and student-centered learning with a visualization map is recommended to facilitate the visualization of complex chemical interconnections and to foster contextual problem-solving skills in chemistry education.